Damage identification of beam‐like structures with contiguous and distributed damage. Issue 4 (23rd March 2012) - RaghuPrasad, B. K.; Lakshmanan, N.; Gopalakrishnan, N.; Sathishkumar, K.; Sreekala, R.
SUMMARY Structural health monitoring of existing infrastructure is currently an active field of research, where elaborate experimental programs and advanced analytical methods are used in identifying the current state of health of critical structures. Change of static deflection as the indicator of damage is the simplest tool in a structural health monitoring scenario of bridges that is least exploited in damage identification strategies. In this paper, some simple and elegant equations based on loss of symmetry due to damage are derived and presented for identification of damage in a bridge girder modeled as a simply supported beam using changes in static deflections and dynamic parameters. A single contiguous and distributed damage, typical of reinforced or prestressed concrete structures, is assumed for the structure. The methodology is extended for a base‐line‐free as well as base‐line‐inclusive measurement. Measurement strategy involves application of loads only at two symmetric points one at a time and deflection measurements at those symmetric points as well as at the midspan of the beam. A laboratory‐based experiment is used to validate the approach. Copyright © 2012 John Wiley & Sons, Ltd.